Legal Reconstruction on the Use of Philantrophic Funds in Supporting State Defense Financing - Efendi, Asral; Madjid, M. Adnan; Ahmad, Irdam; Toruan, Tahan Samuel Lumban (Universitas Islam Negeri Raden Fatah Palembang, 2022)
The collection of public philanthropic funds, especially in financing the national defense sector, has not been clearly regulated, but in the Indonesian context it has considerable potential so that it requires regulations to regulate it. The purpose of this research is to find out how the financing of state defense is in the regulations that govern it currently in Law number 3 of 2002 concerning National Defense, Law number 34 of 2004 concerning the TNI, Law number 23 of 2019 concerning Management of National Resources for Defense. Next, make several alternative suggestions so that philanthropic funds can be used to finance the national defense sector within the framework of Law number 17 of 2003 concerning State Finance and Law Number 1 of 2004 concerning the State Treasury.The research method in this study is normative juridical with a statutory and comparative law approach. With the results there is an opportunity to use community philanthropic funds to participate in financing the national defense sector with a grant mechanism that is still in the APBN mechanism. By looking at the large potential of community philanthropic funds, an ideal concept is proposed that regulates operationally and institutionally.